Simultaneous Determination of Multi Components in Weitongding Particle by HPLC - Tang, Lin; Zhong, Shan (Asian Journal of Chemistry, 2014)
An HPLC method for the simultaneous determination of multi components in Weitongding particle is established. HPLC conditions included Agilent Eclipse XDB-C18 column (4.6 mm × 250 mm, 5 μm) and the mobile phase was a mixture of buffer solution (A, containing 0.1 % formic acid) and methanol (B) at a flow rate of 1 mL min-1 for the gradient elution and the column temperature was maintained at 35 °C. Five active ingredients had good linear relationships: astragalin in the range of 0.0036-0.1800 μg (R2 = 0.9991), quercetin in the range of 0.0045-0.2250 μg (R2 = 0.9992), isorhamnetin in the range of 0.0113-0.5650 μg (R2 = 0.9990), a-tractlone in the range of 0.0108-0.5400 μg (R2 = 0.9993) and hyperoside in the range of 0.0165-0.8250 μg (R2 = 0.9992). Their average recoveries were 95.1 % (RSD = 2.4 %), 93.5 % (RSD = 2.2 %), 96.2 % (RSD = 2.2 %), 94.9 % (RSD = 1.9 %) and 97.6 % (RSD = 3.0 %), respectively. This method was steady with high precision and good repeatability and could be used for the determination of the five active ingredients and quality control of Weitongding particle.